LIVING WITH AGED PARENTS: CHALLENGES AND OPPORTUNITIES - Mahir, Isma Lebbe Mohamed (International Journal of Psychosocial Rehabilitation, 2020)
Population of ageing has been increasing in the modern world today because of the remarkable improvements in life expectancy over the past century. The increase in aged population has multiple implications nearly in all sectors of the society. This study was conducted to identify the challenges and opportunities of living with aged parents in the family. This study was conducted in Akkaraipattu Divisional Secretariat of Ampara district, Sri Lanka. Purposive sample method was used and same size is 40. Interview, focused group discussion and observation methods were used as primary data collection methods and books, magazines, journals, conference proceedings, and reliable web sites were used as the secondary data collection methods of the study. Qualitative data analysis method was used to analyse the data and presented in texts and figures. The study identified 78% of the aged parents are living with their daughters’ family and 22% of the elderly parents are living with their sons’ family. Difficulty in providing traditional family care, difficulty in adaptation, over dependence of aged parents, spending time with aged parents, difficulty in providing health care, financial difficulty, need a specific place with all facilities and difficulty in understanding and handling aged parents were the challenges of living with aged parents. Good source of companionship, good mediators and counsellors, good care takers of grandchildren, safety, help in household activities, religious credits and soul satisfaction and help to gain social respect were the opportunities of living with aged parents.